STRATEGIC DEVELOPMENT OF HIGHER EDUCATION INSTITUTIONS IN THE POST-WAR RECONSTRUCTION OF UKRAINE - Пузирьова, Поліна Володимирівна (Journal of Strategic Economic Research, 2024)
The article examines the main directions of strategic development of higher education institutions (HEI) in the post-war recovery of Ukraine. It is established that higher education institutions are one of the key links in the educational system of Ukraine, which form highly qualified personnel for various sectors of the economy and ensure the scientific and cultural potential of society. It is determined that the strategic development of higher education institutions is a key element of the country's post-war recovery, where the main place is occupied by the creation of a new knowledge infrastructure and the introduction of innovative approaches that will contribute to sustainable development and integration of Ukraine into the global educational environment. It is proved that the post-war reconstruction of Ukraine requires a comprehensive approach, where higher education institutions play a central role in the formation of human capital necessary for the reconstruction of the economy and society. It has been established that the need for strategic development of higher education institutions in Ukraine is caused by global trends, internal challenges and transformation in the country's educational system, which must meet the modern requirements of society, the labor market and global standards of quality education: globalization of education and competition at the global level; training for the modern economy; ensuring the quality of education; improving management efficiency; integration of science and innovation into the educational process; social responsibility and development of society; internationalization of education; and so on. It is determined that the strategic directions of development of higher education institutions are key priorities and measures aimed at modernizing and improving the educational system, improving the quality of education, developing scientific activities, strengthening international relations and integrating into the global educational system. The main strategic directions for the development of higher education institutions are the modernization of infrastructure, restoration of human resources, increasing the financial autonomy of higher education institutions, innovative approaches to education, European integration and international cooperation. The process of HEI transformation is studied and it is found that it is based on the following main aspects: digitalization of the educational process; globalization and international cooperation; integration of education and the labor market; personalization of learning. It is proved that the strategic development of higher education institutions in Ukraine in the post-war period is an important stage for ensuring the country's competitiveness in the international arena and adaptation to the requirements of the modern world with a focus on infrastructure modernization, restoration of human resources, increased financial autonomy, introduction of innovative approaches to education and active integration into the European and world educational space. The implementation of these strategic directions will help to increase the competitiveness of Ukrainian education on a global level and will be the key to the country's sustainable development in the future.